Aplastic Anemia as an Immune-mediated Complication of Thymoma: A Case Report. Issue 7 (October 2018) - Toret, Ersin; Demirag, Bengü; Köker, Sultan A.; Doyurgan, Onur; Ergin, Malik; Genc, Sinan; Karapinar, Tuba H.; Ay, Yilmaz; Oymak, Yeşim; Vergin, Canan
Abstract : Thymomas are the most common masses located in the anterior mediastinum, and they are often associated with autoimmune disorders including myasthenia gravis, polymyositis, and aplastic anemia (AA). Autoreactive T-cell clones generated by the thymoma may lead to autoimmune disorders. We report the case of a 14-year-old boy who was examined for AA, and the underlying cause was determined to be an immune-mediated complication of thymoma. He had no matched sibling donors. He underwent thymectomy, and 3 months later he was treated with immunosuppressive therapy (IST), consisting of antithymocyte globulin and cyclosporine A. The duration of the IST was determined to be a period of 12 months. He has recently been in complete response condition for 6 months since IST stopped. IST is a successful treatment choice for thymomas associated with AA in childhood.